Um corpo como campo de batalha: resistências contemporâneas - Negrini, Carlos Alberto (2018)
This paper analyzes the idea of memory and memory places, terms coined by the French historian Pierre Nora, showing the memory as one of the key elements in the autobiographical creative processes by analyzing Carlos Negrini´s work of performances, photos and video performances. The study describes the construction of the works from referenced realities in the artist's memories and his daily lives exploring the boundaries between subject and society assuming an expressive nature that transits from the intima to the universal. As a consequence of childhood memories and relational conflict with the world, issues such as belonging, rejection, love, hate, identity and sexuality emerge - in the delicate relationship between mother and child. By revealing the body in its multiple possibilities, it assumes a place of extreme political density, evidencing questions to reflect its own existence. This process is a continuity of studies on the development of the author’s identity, considering the homosexuality itself as a starting point along with his strong relationship with his mother, the family as a creative microcosm, raising psychoanalysis issues connected to personal experiences. In a discussion based on pattern how come across a point to selecting what is correct according to the pattern molded by society? After all, apart from the pattern vision must its concept be hidden? A variety of answers will be possible, also, such points will stimulate new ways of thinking, observing and leading to new vision of relating to others and to art. The research aims to provide an overview of the discussed topic, analyze and identify possible factors that influence and are influenced in direct relation memories and images as deflagrate language and artistic expressions. The object will be exposed in the research with the analyzed production, taking into consideration the timing of the work, due to the relationship, often repeated, established between the artistic production.